Didactic strategy for the development of digital competencies in rural high school students - Constante, Jahir Manuel López; Grasst, Yanet Samada (Edelweiss Applied Science and Technology, 2025)
The essential acquisition and development of digital skills in students and teachers is of vital importance for the teaching-learning process. That is why teaching strategies provide a support resource for developing skills that enable effective performance in the digital environment within the educational sphere. The objective of this study was to design a teaching strategy for developing skills in upper elementary students at the San Jacinto Educational Unit, located in a rural area. This study employs a descriptive design with a cross-sectional, non-experimental approach, incorporating both qualitative and quantitative methods. Using the empirical method, a survey was administered to students based on the ECODIES -40 v.2 questionnaire and another to teachers based on the “DigCompEdu Check-In” v.2021 instrument, both validated and based on the European Digital Competence Framework DigComp and DigCompEdu. The results revealed the heterogeneity of digital competencies among the student population in the five areas of digital competency. Among the main findings, the deficiencies presented by students could be a clear indication that educational institutions and other actors in the education system are not assuming their respective roles in the acquisition, development, and strengthening of digital competency skills.